#73: Outcomes of Children with Osteoarticular Infections Treated with Trimethoprim–Sulfamethoxazole. (26th March 2021) - Duvall, Lydia; Platt, Brooks; Kussin, Michelle; Wood, James B
Abstract: Background: Early transition to oral antibiotic therapy for the treatment of children with osteoarticular infections (OAI; osteomyelitis [OM], septic arthritis [SA]) has become increasingly common, yet the choice of optimal regimen remains a challenge. With increasing resistance, poor palatability, and reported allergies to commonly used oral antibiotics, including anti-Staphylococcal penicillins and clindamycin, the treatment options for children with OAI are limited. Trimethoprim–sulfamethoxazole (TMP-SMX) is a commonly used antibiotic, with activity against frequently encountered pathogens causing OAI, yet data regarding outcomes of children with OAI treated with TMP-SMX is limited. Thus, we sought to describe the characteristics and outcomes of children with OAI, at our institution, treated with TMP-SMX. Methods: Records of children aged ≤18 years old, admitted to Riley Hospital for Children between 2010 and 2018, treated with TMP-SMX for acute OAI were reviewed. Patients were identified by ICD-9/-10 codes and order for TMP-SMX. Patients were excluded if they did not receive TMP-SMX for treatment of OAI, had symptoms >30 days, or had an alternative diagnosis. Demographic, clinical, and outpatient/follow-up data were recorded. Treatment was considered successful if the patient completed treatment with TMP-SMX, and there was no evidence of infection at the end of therapy. Treatment failure was defined as the inability to tolerate the medication, development of an infection-related complication, recurrent or chronic osteomyelitis. Additionally, significant adverse drug events were recorded. Results: Eighty-three subjects were identified; however, after screening, 21 subjects were deemed eligible. The majority were non-Hispanic white, males, with a median age of 1.5 years (Interquartile range [IQR], 1–3 years) (Table 1). Twelve patients (57%) had OM, seven (33%) SA, and two (10%) had both OM and SA. A pathogen was recovered in 12 patients (57%), with Staphylococcus aureus being most common. All S. aureus isolates were methicillin resistant, and three were clindamycin resistant. The median duration of intravenous antibiotics prior to discharge was 3 days (IQR 2–4 days). All patients were transitioned to a TMP-SMX containing regimen prior to discharge. The median dose of TMP-SMX was 12.7 mg/kg/day (IQR 11.3–14.9). Reasons for choosing TMP-SMX varied, with the majority (62%) being physician preference. Treatment regimens varied with the majority (62%) receiving TMP-SMX monotherapy. Two patients developed adverse drug reactions attributed to TMP-SMX. Of the 18 patients that completed follow-up, 14 (78%) successfully completed treatment with TMP-SMX. Three patients developed recurrent infections and one patient was unable to finish therapy with TMP-SMX due to developing acute kidney injury. Conclusions: In our study, TMP-SMX was well tolerated; however, only 78% of patients were successfully treated. The majority of treatment failures had prolonged bacteremia due to MRSA perhaps suggesting a higher bacterial burden. The poor outcome in these patients is likely multifactorial, and antibiotic contribution is unknown. TMP-SMX may be a reasonable treatment option for children with OAI when the disease is mild; however, caution should be exercised with severe disease, especially when associated with bacteremia. Prospective, randomized control trials are needed to aid in guideline development and understand the role of TMP-SMX in the treatment of children with OAI.